La percepción de la imagen institucional y su relación con la satisfacción ciudadana en la Municipalidad de Mazán durante el periodo 2025 - Tuesta Ramirez, Berita (2025)
The study examined the relationship between perceived institutional image and citizen satisfaction in the Municipality of Mazán during 2025, using a quantitative, non-experimental correlational design. A representative sample of residents and municipal stakeholders responded to Likert-scale items measuring constructs such as trust, transparency, reputation, operational efficiency, and responsiveness. Spearman correlation analyses revealed a strong and statistically significant link between institutional image and citizen satisfaction (ρ = 0.8791; p = 0.003), along with positive associations between transparency and trust (ρ = 0.711; p = 0.004), reputation and speed of response (ρ = 0.516; p = 0.002), and trust and perceived service quality (ρ = 0.646; p = 0.003). When contrasted with mixed findings from prior regional and educational studies, the results suggest that the strength of the image satisfaction relationship hinges on the alignment between symbolic perceptions and concrete experiences, with transparency and timely responses serving as key legitimacy levers. The evidence highlights that reinforcing both communicative and performance dimensions of institutional image can yield compounded gains in satisfaction, offering actionable insight for improving local governance in Mazán.